2017
DOI: 10.1002/admt.201700130
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Powered, Paper‐Based Electrochemical Devices for Sensitive Point‐of‐Care Testing

Abstract: to enhance the mass transport on the surface of the electrodes and to increase their current response, [5] not requiring external pumps for transporting fluids and offering higher sensitivity and selectivity than other paper-based analytical devices that rely on colorimetric detection. [6] Although the characteristics of PEDs make them especially suited for point-ofcare testing (POCT), these devices-with the exception of blood glucose metersrequire skilled personnel, electric power, and expensive equipment to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 35 publications
(48 reference statements)
0
39
0
Order By: Relevance
“…TENGs have been used as energy harvesters, self‐powered sensors, and power sources for low‐power electronics and wearable devices . When compared with other energy harvesting devices, TENGs offer several advantages, such as high efficiency, large output power, low cost, excellent reliability, and the compatibility with a wide range of materials and simple fabrication processes . TENGs with multilayered electrodes demonstrated to effectively provide steady and high output power to the smart garments to which they are attached .…”
Section: Introductionmentioning
confidence: 99%
“…TENGs have been used as energy harvesters, self‐powered sensors, and power sources for low‐power electronics and wearable devices . When compared with other energy harvesting devices, TENGs offer several advantages, such as high efficiency, large output power, low cost, excellent reliability, and the compatibility with a wide range of materials and simple fabrication processes . TENGs with multilayered electrodes demonstrated to effectively provide steady and high output power to the smart garments to which they are attached .…”
Section: Introductionmentioning
confidence: 99%
“…Typically, triboelectric and piezoelectric effects are two reliable approaches to convert mechanical energy to electricity for wearable electronics. Since the first report of flexible triboelectric nanogenerators (TENGs) by Fan et al, several groups have been involved in applying TENGs on skin‐inspired sensors, targeting at the realization of battery‐free monitoring and diagnostic systems . For instance, Pu et al reported a mechnosensational TENG (msTENG)‐based noninvasive micromotion sensor that is capable of translating eye blink into control command based on a multifilm structure, which could be flexibly mounted behind an eyeglass arm ( Figure a) .…”
Section: Multifunctional Skin‐interfaced Wearable Devicesmentioning
confidence: 99%
“…c) Schematics of the charge generation process in the TENG attached to the bottom of the microfluidic layer. Reproduced with permission . Copyright 2017, WILEY‐VCH.…”
Section: Diversity Of Flexible Electronics Based On Paper Matricesmentioning
confidence: 99%
“…Similarly, such device can also be applied to antifouling since the pulse electricity generated by the device can prevent algae (e.g., Dunaliella and Navicula ) from adhering to metallic substrates. By integrating a triboelectric generator with paper microfluidic, Martinez and co‐workers demonstrated self‐powered, electrochemical devices for sensitive POC testing . As illustrated in Figure c, wicking‐based microfluidic channels for accurate colorimetric assays and self‐pipetting test zones for electrochemical determination on the top layer were constructed via wax printing approach.…”
Section: Diversity Of Flexible Electronics Based On Paper Matricesmentioning
confidence: 99%